1981
DOI: 10.1002/pssb.2221050163
|View full text |Cite
|
Sign up to set email alerts
|

On the Band Structure of CdGa2S4

Abstract: BYThe band structure of CdG%S4 is calculated by the pseudopotential method in /1/ and by the method of localized orbitals in /2/. According to the data of /1/ the top of the valence band meets the r2v representation, whereas according to /2/ it complies with r3v+ r4v. The conduction band bottoms in /1/ and /2/ a r e conform to the TlC representation.ly obtained data on the nature of optical transitions and their values in the fundamental absorption edge region a r e conflicting. In /6/ the reflection spectra w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…For further analysis of the optical data a number of useful, associated relations can be derived that link the real and imaginary parts of the dielectric function and the optical constants, that is, the so-called dispersion relation and sum rules, which have been extremely valuable in analysing and testing optical constant data. The dispersion relation for CdGa 2 Se 4 films is described well by a single-term Sellmeier oscillator [25]: Assuming that the high frequency properties of CdGa 2 Se 4 could be treated as that for a single oscillator of an empty lattice at infinite wavelength, λ −1 → ∞, and applying the simple classical dispersion relation [24], the value of the highfrequency dielectric constant, ε ∞ estimated from figure 5 using this procedure was found to be 6.78, in good agreement with the value of ε ∞ = 6.7 for E⊥C determined from the reflection spectra of CdGa 2 Se 4 single crystals [26] and slightly less than 7.29, determined from the optical phonon spectra of CdGa 2 Se 4 [27].…”
Section: Optical Constant Refractive Index Dispersion and Sum Rulessupporting
confidence: 60%
See 1 more Smart Citation
“…For further analysis of the optical data a number of useful, associated relations can be derived that link the real and imaginary parts of the dielectric function and the optical constants, that is, the so-called dispersion relation and sum rules, which have been extremely valuable in analysing and testing optical constant data. The dispersion relation for CdGa 2 Se 4 films is described well by a single-term Sellmeier oscillator [25]: Assuming that the high frequency properties of CdGa 2 Se 4 could be treated as that for a single oscillator of an empty lattice at infinite wavelength, λ −1 → ∞, and applying the simple classical dispersion relation [24], the value of the highfrequency dielectric constant, ε ∞ estimated from figure 5 using this procedure was found to be 6.78, in good agreement with the value of ε ∞ = 6.7 for E⊥C determined from the reflection spectra of CdGa 2 Se 4 single crystals [26] and slightly less than 7.29, determined from the optical phonon spectra of CdGa 2 Se 4 [27].…”
Section: Optical Constant Refractive Index Dispersion and Sum Rulessupporting
confidence: 60%
“…Single crystals of CdGa 2 Se 4 were prepared using the chemical transport reaction technique, with iodine as a transport agent [10][11][12]. X-ray diffraction analysis showed that CdGa 2 Se 4 single crystals crystallized into tetragonal structures with the space group S 4 2 and the lattice parameters were a = 5.73 1 Å, b = 10.75 1 Å, [13].…”
Section: Introductionmentioning
confidence: 99%
“…Cd 1-x Co x Ga 2 S 4 is a new quaternary solid solution based on CdGa 2 S 4 and,CoGa 2 S 4 which are ternary compounds with the general formula AB 2 C 4 . The CdGa 2 S 4 is a wide-gap semiconductor (E g = 3.5 eV at 300 K) with high photoconductivity and strong luminescence in the visible region [1,2]. Also, CoGa 2 S 4 belongs to the class of materials referred to as semimagnetic semiconductors or diluted magnetic semiconductors [3].…”
Section: Introductionmentioning
confidence: 99%
“…1 Introduction CdGa 2 S 4 is a wide-gap semiconductor (Eg = 3.5 eV at 300 K) with high photoconductivity and strong luminescence in the visible region [1][2][3][4]. These desirable properties make this compound a promising optoelectronic material.…”
mentioning
confidence: 99%